2015
DOI: 10.1159/000369810
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Granulomatosis: Clinical Signs of Different Pathologies

Abstract: Orofacial granulomatosis (OFG) is an uncommon disease characterized by persistent or recurrent soft tissue enlargement, oral ulceration and a variety of other orofacial features. It could be an oral manifestation of a systemic disease. For a correct differential diagnosis, local and systemic conditions characterized by granulomatous inflammation should be excluded using appropriate clinical and laboratory investigations. In fact, the diagnosis of OFG may be confirmed only by histopathological identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 61 publications
3
43
0
Order By: Relevance
“…Because of involvement of OFG in CD and sarcoidosis, the possible role of infections in the pathogenesis of OFG has been suggested [17]. Several studies have suggested that there is no conclusive evidence to support the role for allergy in OFG [18]. Recently, a monoclonal lymphocytic expansion in OFG lesion has been identified that may be responsible for the granuloma formation through cytokine production in lesions [19,20].…”
Section: Etiologymentioning
confidence: 99%
“…Because of involvement of OFG in CD and sarcoidosis, the possible role of infections in the pathogenesis of OFG has been suggested [17]. Several studies have suggested that there is no conclusive evidence to support the role for allergy in OFG [18]. Recently, a monoclonal lymphocytic expansion in OFG lesion has been identified that may be responsible for the granuloma formation through cytokine production in lesions [19,20].…”
Section: Etiologymentioning
confidence: 99%
“…Troiano et al explored the role of infections and genetics in the MRS etiology [21]. The two main pathogens investigated were Mycobacterium tuberculosis and Borrelia burgdorferi.…”
Section: Complete Blood Countmentioning
confidence: 99%
“…The two main pathogens investigated were Mycobacterium tuberculosis and Borrelia burgdorferi. The skin biopsies were positive for M. tuberculosis but controversial for B. burgdorferi [21]. Trials of treating MRS with anti-tuberculosis regimens have not appeared in literature.…”
Section: Complete Blood Countmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic bowel disease, concurring or developing over the course of the disease, is reported in up to 50% of cases [1]. Nonspecific signs of extraintestinal Crohn's disease such as mucogingivitis, cobblestone-like mucosa, and lip swelling with vertical fissures or deep linear ulcers precede the intestinal symptoms in about one-third of affected patients [4,5].…”
mentioning
confidence: 99%